Applying corporate social responsibility principles to the church : a case study of the interface between the Indian Pentecostal/Charimatic Church in the Phoenix Community, Durban North (KwaZulu Natal) and social responsibility - Francis, Virginia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2008.